'Anarchitecture' As An Oppositional Position in Architecture - Uluengin, Oze; Gorgulu, Tulin (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2014)
Beginning from the earliest traditional tales, the notion of space has been conceptualized in a variety of ways. Throughout history, these conceptualisations have undergone transformation on a parallel with turning points in thought systems, and thus space has found a place for itself in all varying architectural approaches. In the first part of this study, the notion of 'anarchitecture', which emerged in the last quarter of the 1900s to fervidly criticize the de facto understanding of architecture, is approached through the works of three distinguished researchers in this field. The first section evaluates both the comprehension of space expressed in the installations performed by Gordon Matta-Clark, the renowned artist who has substantial works on anarchitecture, and the fundamental principles he sought to destroy. This is followed by the 'free space' concept of Lebbeus Woods, who is well-known for approaching anarchitecture in a more theoretical manner. The final section of the first part of the study examines the understanding of Brian Heagney, who has explored anarchitecture through the concept of space in primitive communities. In the second part of the study, an attempt is made at analyzing the understanding of space of all these different approaches. The objective of this work is to evaluate and emphasize the contributions of anarchitecture to our present-day understanding of space.
Keywords: Anarchitecture; Brian Heagney; Gordon Matta-Clark; Lebbeus Woods; space; Architecture